2020
DOI: 10.3390/nu12092785
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Bioenergetics, and Metabolic Syndrome

Abstract: According to the World Health Organization (WHO), the global nutrition report shows that whilst part of the world’s population starves, the other part suffers from obesity and associated complications. A balanced diet counterparts these extreme conditions with the proper proportion, composition, quantity, and presence of macronutrients, micronutrients, and bioactive compounds. However, little is known on the way these components exert any influence on our health. These nutrients aiming to feed our bodies, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 325 publications
(365 reference statements)
1
31
0
4
Order By: Relevance
“…As it is known, several markers have been proposed in order to measure biological rather than chronological aging [ 6 ], unless we are far from having specific and reliable biomarkers of biological aging, several molecules and pathways have been described as possible biomarkers of senescence. Amongst these different biomarkers some have been related to metabolic deregulation and associated to high metabolic risk profiles as telomeres length [ 7 8 ], DNA epigenetic modifications [ 9 ], and mitochondrial dysfunction [ 10 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…As it is known, several markers have been proposed in order to measure biological rather than chronological aging [ 6 ], unless we are far from having specific and reliable biomarkers of biological aging, several molecules and pathways have been described as possible biomarkers of senescence. Amongst these different biomarkers some have been related to metabolic deregulation and associated to high metabolic risk profiles as telomeres length [ 7 8 ], DNA epigenetic modifications [ 9 ], and mitochondrial dysfunction [ 10 ].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…A constellation of risk factors for cardiovascular disease is called metabolic syndrome (MetS), whose determining factors are, in order of importance: weight, genetics, ageing and lifestyle [154]. The criteria for defining MetS are based on the presence of 3 out of 5 factors, including obesity, elevated triglycerides, reduced HDL-C, elevated blood pressure and elevated fasting glucose [155].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…It has been shown that individuals with these characteristics are also commonly prone to a chronic, low-grade inflammatory states. Oxidative stress phenomena are also involved in MetS, probably due to the disturbance of the nutrient metabolism at the mitochondrial level [154].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Dysregulation of mitochondrial function by various internal and external stimuli leads to suppression of energy supply and induction of apoptosis. UV radiation and laser irradiation are the most representative external stimuli in such pathological processes [ 128 , 129 ]. UV and laser irradiation promote oxidative stress by enhancing ROS production [ 130 , 131 ].…”
Section: Photodynamic Therapymentioning
confidence: 99%